TOUCHES ON THE EUROPEAN CHARACTER OF BULGARIAN LITERATURE - Vanya Dobreva (Издател)
Monograph of Prof. Tsvetana Georgieva, DSc “The Literary Secession: the Bulgarian Belle Époque” is a serious study on the aesthetics of modernism – the practice of the Secession/Decorativism style artistic use in Bulgarian literature. Motifs, images, concepts, ideologies, etc. are studied and presented typological for the Secession/Decorativism, which underlines the importance of the book of a respectful serious work on the development of for the Secession/Decorativism in Bulgaria.